Serum laminin γ2 monomer as a novel diagnostic and prognostic marker for pancreatic ductal adenocarcinoma - Takeshi Terashima; Kouki Nio; Naohiko Koshikawa; Makoto Ueno; Tadashi Toyama; Masaki Miyazawa; Tomoyuki Hayashi; Akihiro Seki; Hidetoshi Nakagawa; Noriho Iida; Shinya Yamada; Hajime Takatori; et al. (BJC Reports)
Abstract Background The identification of effective diagnostic and prognostic biomarkers is critical to improving the outcomes of patients with pancreatic ductal adenocarcinoma (PDAC). We explored the potential of serum levels of laminin γ2 monomer (LG2m) as a biomarker in PDAC. Methods This study included two cohorts. Cohort 1 included 142 PDAC patients, 55 patients with intraductal papillary mucinous neoplasm (IPMN), and 46 healthy individuals. Cohort 2 included 518 PDAC patients. The medical records of patients were reviewed. Cut-off levels for LG2m were determined by receiver operating characteristic analysis. Results In Cohort 1, serum LG2m levels were significantly higher in PDAC patients compared with healthy individuals (P < 0.001) and IPMN patients (P < 0.001). Comparing PDAC patients and health individuals, the optimal cut-off level of LG2m was 9.55 pg/mL and the sensitivity, specificity, and area under the curve were 0.89, 0.87, and 0.88, respectively. High sensitivity of LG2m in PDAC patients were confirmed in Cohort 2. The sensitivity and specificity of LG2m was higher than that of CEA and CA19-9. In patients treated with resection or chemotherapy, high serum LG2m level indicated a significantly shorter survival (P = 0.042 and P < 0.001, respectively). Conclusions LG2m may be a useful diagnostic and prognostic marker for PDAC.